A pessoa física como sujeito passivo do ICMS-Importação: a inconstitucionalidade da Emenda Constitucional nº 33/2001 - Cordeiro, Ricardo de Assis Souza (2013)
The ICMS-Import is a very important tax-Import existing in our legal system. This is so because and due to globalization and the ease of negotiations for transactions involving imports of goods are increasingly present in our real ty. Thus, because it is a tribute, to their correct implementation and collection are as umptions which the legislature cannot get away with. However, the strange thing is when it tries to tax through the ICMS-Import the entry of goods imported by individuais' non taxpayers to this exaction, because the concepts of products and goods are not confused. Still, as amended by Constitutional Amendment. 33/2001 extrapolated the limits onferred the derived constituent power, violated the Constitution in many ways, given that this injured fundamental right of taxpayers and contradicted devices expressed in constitutional text, creating a new tax on imports. Thus, we shall see that the ICMSimport on goods imported by individuais' non taxpayer does not hold up under any . circumstances due to its clear unconstitutionality